Mikael the secret adventure / Muhammad Ameer Imran Mohd Radi - Mohd Radi, Muhammad Ameer Imran (Universiti Teknologi MARA, Kedah, 2025)
Mohammad Eizwan Eizaidie bin Matheus. also known as Lukiesan. is a comic illustrator from Sabah, Malaysia, who started his journey in 2019. He is most recognized for his mango-inspired, black-and-white superhero comics, which have gained popularity on platforms like lnstagram and Face book. Lukiesan 's artwork is known for its unique character designs and exciting action sequences. With Mikael: The Secret Adventure. Lukiesan is stepping away from the superhero genre to explore new creative territories. This new comic will feature vibrant colors and different character styles. showcasing his ability to adapt and push his artistic boundaries. Mikael: The Secret Adventure follows Mikael, a 14-year-old tech genius, who lives alone on his father's estate after his father. a scientist. mysteriously disappeared. One day, Mikael receives a letter addressed to his father. which leads him to discover a dangerous experiment carried out by a secret organization. Mikael believes his father is still alive and sets off on a journey to stop the organization's evil plans. Along the way, Mikael teams up with a group of raccoons, Leo, Laila, and Nico, who are also working to stop the organization. Using his tech skills, Mikael creates gadgets and suits to help the raccoons uncover the truth behind the experiments. Together, they face dangerous creatures, sabotage the organization's toxic experiments, and race to stop the project before it spirals out of control. Mikael: The Secret Adventure is a thrilling mix of action, mystery, and technology. The comic explores themes of bravery, teamwork, and how technology can be used to make a difference in the world. It's an exciting, fast-paced adventure with plenty of twists and turns to keep readers on the edge of their seats.